Testing the Activity of A Preparation of Katuk Leaf (Sauropus androgynus (L.) Merr.) Ethanol Extract Ointment on the Healing of Cut Wounds in Rabbits - Poppy Ayu Holy Fitriana; Supriyanto Poppy Ayu Holy Fitriana; Wahyu Purwanjani (Pratama Medika : Jurnal Kesehatan, 2023)
Sauropus androgynus (L.) Merr. leaves are plants that contain secondary metabolite compounds that can be used as medicine in healing cuts. Objective: to determine the ethanol extract ointment of katuk leaves (Sauropus androgynus (L.) Merr.) for healing cuts in rabbits. Methode: the preparation of ointment preparations using the ethanol extract of katuk leaves (Sauropus androgynus (L.) Merr.) is identified for the compound content first then the ointment preparations are made. Tested using 3 (three) rabbits with 5 treatment groups, namely 10%, 12.5%, 15% katuk leaf ethanol extract ointment, positive control (10% povidone iodine), negative control (no extract base). All rabbits were injured with a length of 2cm to a depth of ± 0.2cm, each rabbit received 5 incision points. The wound is smeared 2 times a day every morning and evening. Wound observations were carried out every day for 14 days. Results Data analysis was carried out using One-Way ANNOVA. Results: Katuk leaf ethanol extract contains flavonoids, saponins and tannins. All ointment formulations have activity in healing cut wounds even though they have different healing times. Katuk leaf ethanol extract ointment meets the physical quality test requirements for ointments. The statistical test results showed that there was a significant difference in the healing of cut wounds in rabbits, namely (p<0.05). Conclusion: Katuk leaf ethanol extract ointment with a base concentration of 15% has the most optimal potential for healing cuts in rabbits.